Macaw's encyclopedia of pipeline defects. (Tiratsoo Technical ; Clarion Technical Publishers, 2014)
The aim of this second edition of MACAW's Encyclopedia (the first edition of which was published as MACAW's Pipeline Defects) is to illustrate the range of defects that may be encountered in high-pressure steel pipelines and their pipeline coatings. It gives advice on the probable cause and significance of the defects and comments on appropriate remedial actions.
Keywords: Pipeline failures.; Pipelines -- Design and construction.; Pipe, Steel.; elektronické knihy; electronic books